Compost Science & Utilization - Compost Science & Utilization (Taylor & Francis, 2026)
Compost Science & Utilization is a quarterly peer-reviewed journal that reports on advancements and breakthroughs in the science and engineering of compost production, compost product quality, and the utilization of composted materials. The journal will consider articles on the following; compost microbial ecology; novel feed stocks; odor reduction and control; contaminant issues and mitigation; compost analysis techniques; plant disease suppression using composts; compost fertility; composting as part of integrated biorefineries; pathogens and composting; compost and soil quality; bioremediation via composting; composting as a tool to address climate change and other topics.
FI 0.31
Q3
Keywords: Biological; Earth & Environmental Food Science; Acuerdos transformativos; Transformative agreements; Calidad del compost; Fertilidad del suelo; Biorremediación; Microbiología del compost